2020
DOI: 10.1177/0018726720909864
|View full text |Cite
|
Sign up to set email alerts
|

The stories that make us: Leaders’ origin stories and temporal identity work

Abstract: The stories we tell about our origins can shape how we think and act – helping us make sense of and communicate who we have “become” over time. To better understand the role that origin stories play in individuals’ work lives, we explore how 92 men and women leaders make sense of “becoming” a leader (origin stories) and “doing” leadership (enactment stories). We find that, despite the uniqueness of their experiences, their narratives converge around four frames, being, engaging, performing, and accepting, thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 78 publications
0
47
0
3
Order By: Relevance
“…Though still acknowledging the social nature of leader emergence, other approaches to understanding this important phenomenon have been more leader centric and focused on the prospective leader making sense of and claiming the leader role. Using a narrative perspective, Zheng et al (2021) introduced four frames (being, engaging, performing, accepting) that prospective leaders use as they navigate the emergence process. These frames allow the prospective leader to understand, articulate, and enact their identity as a leader (Zheng et al, 2021).…”
Section: Question 1: What Do We Know About the Phenomenon Of Leadersh...mentioning
confidence: 99%
“…Though still acknowledging the social nature of leader emergence, other approaches to understanding this important phenomenon have been more leader centric and focused on the prospective leader making sense of and claiming the leader role. Using a narrative perspective, Zheng et al (2021) introduced four frames (being, engaging, performing, accepting) that prospective leaders use as they navigate the emergence process. These frames allow the prospective leader to understand, articulate, and enact their identity as a leader (Zheng et al, 2021).…”
Section: Question 1: What Do We Know About the Phenomenon Of Leadersh...mentioning
confidence: 99%
“…In an early statement of this enthusiasm, Sveningsson and Alvesson (2003: 1163–1164) suggested that identity is ‘central for issues of meaning and motivation, commitment, loyalty, logics of action and decision-making, stability and change, leadership, group and intergroup relations, organizational collaborations, etc.’. There are now many empirical studies that connect identity issues to knowledge management (Kamoche et al, 2014), organizational routines (Brown and Lewis, 2011), power relations and organizational politics (Koveshnikov et al, 2016), morality/ethics (Weaver, 2006), entrepreneurship (Essers and Benschop, 2009), boundary spanning (Ellis and Ybema, 2010), leadership (Zheng et al, 2020), issues of temporality (Kuhn, 2006) and legitimacy (Brown and Toyoki, 2013) among many others. One rich vein of empirical research analyses how the identity work engaged in by individuals and groups is also a form of institutional work (Creed et al, 2010; Lok, 2010; Seo and Creed, 2002).…”
Section: The Identity Work Perspectivementioning
confidence: 99%
“…Internalizing a leader identity has been described as a process of both claiming and granting an identity as a leader (DeRue and Ashford, 2010), and the onus to claim a leader identity may even be stronger for women than for men (Zheng et al, 2020). The success of women's ability to identify as leaders is an important first step in their development and our ability as a society to close the gender gap.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work suggests that leader identity work may be gendered. Through a qualitative study of origin and leadership enactment narratives, Zheng et al (2020) revealed that men utilize "performing" frames of leadership such that they rely more on formal positions and a sense of duty or responsibility in the building and maintenance of their leadership identity, whereas women utilize "engaging" frames more often which highlight leader-like activities and a more facilitative approach to leading. Applying DeRue and Ashford's (2010) theory, the authors posit that men may receive more leadership grants through formal positions, whereas women may rely more on leadership claims through actions.…”
Section: Leader Identity Developmentmentioning
confidence: 99%